2022
DOI: 10.1177/08903344221076539
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir and Human Milk: A Case Study

Abstract: Introduction: Remdesivir was originally developed to treat Ebola hemorrhagic fever, and its efficacy in treating coronavirus disease 2019 was detected during a preliminary analysis of a randomized controlled trial. It is known that Severe Acute Respiratory Syndrome Coronavirus 2 is not transmitted through human milk, but data about the presence of remdesivir in human milk have been lacking. Main issue: In this case study, we determined the human milk-to-serum drug concentration ratio and the relative dose of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A study reported the concentration of remdesivir metabolite GS-441524 in maternal serum was 33.1–389.9 ng/ml and in human milk was 13.50–284.9 ng/ml. The half-lives of GS-441524 in maternal serum and milk were 25.1 and 9.3 h respectively ( Wada et al, 2022 ). Therefore, it is urgent to evaluate the efficacy of remdesivir in pregnant patients, which requires more clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported the concentration of remdesivir metabolite GS-441524 in maternal serum was 33.1–389.9 ng/ml and in human milk was 13.50–284.9 ng/ml. The half-lives of GS-441524 in maternal serum and milk were 25.1 and 9.3 h respectively ( Wada et al, 2022 ). Therefore, it is urgent to evaluate the efficacy of remdesivir in pregnant patients, which requires more clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…A 28-year-old primipara after delivery 2 days who was diagnosed with COVID-19, and then she was given remdesivir. The remdesivir concentration in maternal serum and breast milk was measured, and the ratio of drug concentration in milk to serum was low (0.089), as was the relative infant dose (0.0070%), which suggested that breastfeeding was safe during treatment with remdesivir and can be expected to protect the infant from infection ( Wada et al, 2022 ).…”
Section: The Efficacy Of Remdesivir In Covid-19mentioning
confidence: 99%
“…Figure 3 illustrates the mechanism action of in vivo SARS-CoV-2 inhibition of Remdesivir. It has been suggested that GS-441524, a precursor compound phosphorylated to GS-443902, inhibits SARS-COV-2 both in vitro and in vivo and is a superior compound for treating COVID-19 [53,54] . Brunotte and Schloer et al [55] found that GS-441524 and fluoxetine displayed good tolerance and antiviral effects against SARS-CoV-2 variants.…”
Section: Remdesivir's Action Mechanism Against Sar-cov-2mentioning
confidence: 99%
“…[14] It is particularly important to track and adjust the dosage of drugs used by patients after infection with COVID-19, as blindly conforming to the previous dosage may lead to subtherapeutic or toxic effects. [15,16] Meanwhile, since DDI may exist between different drugs, leading to unpredictable drug levels in the body, dose adjustments should be made according to individuals. [17] Therapeutic drug monitoring (TDM) is crucial for the effectiveness and safety of treatment.…”
Section: Introductionmentioning
confidence: 99%